2021
DOI: 10.1016/j.artd.2021.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes After Total Hip Arthroplasty in a Low-Resource Country by a Visiting Surgical Team

Abstract: Background: Total hip arthroplasty (THA) is a highly successful procedure but limited in many lowresource nations. In response, organizations globally have conducted service trips to provide arthroplasty care to underserved populations. Few outcomes data are currently available related to these trips. Our study aims to demonstrate the feasibility of tracking patient-reported outcomes and complications after THA in a low-resource setting and that outcomes are comparable to those in developed countries. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
(39 reference statements)
0
11
0
Order By: Relevance
“…The weighted follow-up rate was 57.5%. The majority reported in-person follow-up (83%) while three (16.7%) used technology-based platforms (SMS or phone calls) [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The weighted follow-up rate was 57.5%. The majority reported in-person follow-up (83%) while three (16.7%) used technology-based platforms (SMS or phone calls) [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…overwhelmed facilities [31] or a lack of a patient database [42]). However, the most commonly identified barrier was cost of follow-up to patients, both monetary and time costs, identified in six (22%) studies [25,26,28,[39][40][41]. Cost was primarily reported as it relates to financial assistance for patients (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Second, with the main outcome of PPSP occurrence as a categorical variable, it is also possible that we missed certain constructs of PPSP as captured by multidimensional or descriptive tools, such as PROMs 66 after hip and knee arthroplasty which has been well described elsewhere. 40 , 44 , 61 , 117 , 124 , 130 Third, this review included data both from studies on THR and TKR, although the literature has shown that pain and patient satisfaction outcomes from THR are generally better in comparison with TKR. 64 However, we analyzed the data separately, where possible.…”
Section: Discussionmentioning
confidence: 99%